Sistem kolektivne varnosti OZN v novem varnostnem okolju - Grizold, Anton (Teorija in praksa, 2016)
In today's security environment, internal conflicts represent the main threat to international peace and security and to the existing collective security system provided within the framework of the United Nations (UN). This article analyzes the positive effects of the functioning of mechanisms and instruments of the UN's collective security system in resolving the crisis in Libya. This article confirms that the collective security system implemented within the UN, and supplemented by a mechanism of responsibility to protect, is still an adequate security system for the international community to ensure international peace and security. However, new emphasis should be placed on post-conflict peace-building mechanisms.
Keywords: International organizations; International security; kolektivna varnost; Mednarodna varnost; Mednarodne organizacije; Military conflicts; OZN; Vojaški konflikti